O direito fundamental à imagem na persecução penal brasileira - Maia, Daniel (2011)
The current Democratic State of Right in which Brazil is inserted does not allow any violence against individual rights and guarantees, since such rights and guarantees are based on human dignity. Thus, it must be assured to everyone, even to those who are being criminally prosecuted by the state, either because they are under investigation in police procedures, or because they are being criminally prosecuted, that their dignity is respected in totum. What happens is that various segments of media have great interests in the exacerbated exploitation of the image of criminally investigated and prosecuted prisoners, using it in a disproportionate way, always aiming at commercial profit and high audience levels, which these stories already get. On the other hand, the population, mostly uninformed and unaware that the violation of fundamental rights and guarantees represents a violation of the legal order itself, gets outraged when the State takes measures to protect the image of the criminally pursued. In addition to all of this, there is still the conflict between the constitutional principles of freedom of expression and information on one side, and the rights to image and to human dignity itself on the other. Therefore, this study shows that the image rights, for being fundamental rights and, thus, obviously, based on human dignity, cannot be violated, at most being subject to withdrawal, with the possibility of exhibition of the image of those involved in criminal prosecution, only in exceptional cases and with previous justified judicial sentence.